Collapsed wall: destructive and reconstructive surgery of anterior abdominal wall tumour in a young girl. Issue 2 (8th February 2019) - Che Ghazali, Khairunnisa; Mazian, Haniif Ahmad; Keat, Kim Choon; Kai, Michael Wong Pak; Md Hashim, Mohd Nizam; Zakaria, Andee Dzulkarnaen; Zain, Wan Zainira Wan; Zakaria, Zaidi; Saad, Arman Zaharil Mat; Sulaiman, Wan Azman Wan; Zaidi, Nurul Atiqah Ahmad; Jaafar, Hasnan
ABSTRACT: Natural history of abdominal wall soft tissue sarcoma is still poorly understood due to its rarity. In unpublished data of our institution, only seven cases of abdominal wall soft sarcoma with ICD-10 coding of 49.4 were found for past 10 years. We illustrate a case of juvenile fibrosarcoma of anterior abdominal wall. This is a case of young girl with anterior abdominal wall tumour, underwent wide local excision with immediate reconstruction. There are few options of surgical treatment for this case, but which is the best. It is always a challenge in managing young patient with giant abdominal wall defect in view of long term effect namely weakened abdominal wall, pregnancy related issue and risk of herniation and surgical site recurrence as well.